Climate Change Contributing towards the Worsening of Environment (International Journal of Innovative Research in Computer Science & Technology, 2022)
The authors reviewed a study in which the  researchers used the example of the 2000 presidential  election in the United States to demonstrate that political  disputes with technology foundations do not resolve  themselves via technological methods. On the other hand, I  investigate the assumption that scientific investigation is  inevitably politicized in environmental debates using  examples like changing climate, genetic modification, and  nuclear waste disposal. I'm going to look at three possible  reasons for this. Second, science provides essential valid  knowledge about existence to the contending parties of their  own bodies, which are chosen in part because they assist in  making sense of human wants and moral systems, as well as  being rationalized as a result of this information. For a  second, opposing disciplinary methods may be causally  linked to rival political or ethical views that are founded on  differing values, in order to explain the scientific origins of  an environmental dispute.
Keywords: Biodiversity; Climate Change; Environment; Land Degradatio; Nature